Heritage narrative and memorial devices in Colonia del Sacramento - Ibarlucea, Laura (2020)
The heritage repertoire in the historic quarter of Colonia del Sacramento is configured around a set of marks, both discursive as material. These tangible and intangible elements operate as support of story and constitute a collection that articulates a narrative, both patrimonial and touristic. This article will attempt to clarify how these assets can be understood as devices and, in that way, they model the manners which space is perceived and acted upon. For this purpose, the concept is defined by explaining how it applies to ways to activate memory. Once defined, it has identified some elements, both tangible and intangible, that can be considered memorial devices for the study case developing in what sense and how they operate.